2014
DOI: 10.1128/jcm.00870-14
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic Adenoid Is a Major Infection Site of Human Bocavirus 1

Abstract: e Human bocavirus 1 (HBoV1) is associated with respiratory infections worldwide, mainly in children. Similar to other parvoviruses, it is believed that HBoV1 can persist for long periods of time in humans, probably through maintaining concatemers of the virus single-stranded DNA genome in the nuclei of infected cells. Recently, HBoV-1 was detected in high rates in adenoid and palatine tonsils samples from patients with chronic adenotonsillar diseases, but nothing is known about the virus replication levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
1
17
1
Order By: Relevance
“…Antibiotics are generally not sufficient modes of treatment for adenoid hypertrophy, as many infections are characterized by highly resistant bacteria that do not respond to many groups of antibiotics [74,75]. Additionally, many viruses are often associated with adenoid hypertrophy, including human bocavirus [76,77], EBV, and polymoviruses [76].…”
Section: Non-surgical Therapy For Adenoid Hypertrophymentioning
confidence: 99%
“…Antibiotics are generally not sufficient modes of treatment for adenoid hypertrophy, as many infections are characterized by highly resistant bacteria that do not respond to many groups of antibiotics [74,75]. Additionally, many viruses are often associated with adenoid hypertrophy, including human bocavirus [76,77], EBV, and polymoviruses [76].…”
Section: Non-surgical Therapy For Adenoid Hypertrophymentioning
confidence: 99%
“…Since the identification of human bocavirus 1 in nasopharyngeal aspirates in 2005, evidence is increasing that the HBoV1, belonging to the Bocaparvovirus genus of the Parvoviridae family, is associated with respiratory tract infections and gastrointestinal infections ( Allander et al, 2005 ; Huang et al, 2012 ). It is presumed that besides causing acute infections HBoV is persisting in a replicative but subclinical state, and is a pathogen rather than an innocent bystander ( Proenca-Modena et al, 2014 ). Previous studies suggest that HBoV is associated with some lung and colorectal tumors and prove that the bocavirus persistence is increased in cancer patients ( Schildgen et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that HBoV persists in adenotonsillar tissue, which is considered as the major replication site in vivo by some researchers ( Clement et al, 2009 ). Proenca-Modena et al (2014) detected human bocavirus in 31.1% of 172 hypertrophic adenoids or tonsils from children. Szalmas et al (2013) reported that the presence of HBoV displays a statistically significant correlation to Otitis media with effusion cases associated with adenoid hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…7 Obstructive hypertrophy results from increase in immunologic activity while infection of the tonsils leads to inflammation of tonsillar tissue. 8,9 Hypertrophic tonsils may be acute or chronic and account for about 80% of obstructive sleep apnoea in children. 10 Severe forms of obstructive sleep apnoea due to adenotonsillar hypertrophy may be complicated by pneumonia, cor pulmonale, pulmonary hypertension, chronic hypercapnia or hypoxia and right heart failure.…”
Section: Introductionmentioning
confidence: 99%